INOVASI PENANAMAN BIBIT AREN UNTUK KONSERVASI DI BANTARAN SUNGAI BATANG HARI DI NAGARI SUNGAI DAREH KABUPATEN DHARMASRAYA - Zahlul Ikhsan; Indra Dwipa; Yaherwandi Yaherwandi; Reflinaldon Reflinaldon; Edwin Edwin; Dewi Rezki; Irwin Mirza Umami; Siska Efendi; Wulan Kumala Sari; Dede Suhendra (LPPM Universitas Andalas, 2021)
Nagari Sungai Dareh, Pulau Punjung District, Dharmasraya Regency is an area located on the banks of the Batang Hari River. Rivers must be protected and conserved, and their functions and benefits must be improved for the health and sustainability of the ecosystem. Planting sugar palm on the river banks is one way that can be done to preserve the river. Besides being useful for conservation, sugar palm also has a high economic value. This activity aims to empower the community by 1) Conservation activities on the banks of the Batang Hari river, and 2) Introduction of sugar palm plants and increasing community knowledge and skills in sugar palm cultivation. This activity was carried out in Jorong Sungai Kilangan Nagari Sungai Dareh, Dharmasraya Regency, with lectures, discussions, and demonstrations of planting sugar palm on the banks of the river. The number of students involved was five people. The people of Nagari Sungai Dareh are very enthusiastic about listening and discussing sugar palm cultivation and the importance of river conservation. Most of the participants are very interested and will immediately plant sugar palm on their land, but some are still learning more. As a form of our hope that the planting of sugar palm on the river banks can be successful, we assist ± 200 sugar palm seeds for the people of Nagari Sungai Dareh. Community empowerment through sugar palm cultivation has been able to increase community knowledge and skills about the importance of maintaining river sustainability and the prospects and challenges of sugar palm cultivation.